Menyongsong Harmoni: Pergulatan Sejarah, Akulturasi, dan Potensi Vihara Amurva Bhumi Blahbatuh, Gianyar sebagai Sumber Blajar Sejarah SMA - Putu Eka Audria Maharani; Desak Made Oka Purnawati; I Putu Hendra Mas Martayana (Universitas Pendidikan Ganesha, 2025)
This research seeks to reveal how historical struggles and civilizational interactions between Chinese ethnicity, Buddhism and localities are manifested in monastery artefacts. Therefore, this research aims to: (1) understand the history of the establishment of Vihara Amurva Bhumi Blahbatuh, (2) identify forms of cultural acculturation occurring in Vihara Amurva Bhumi Blahbatuh, and (3) explore the values of Vihara Amurva Bhumi Blahbatuh that have the potential to be used as a historical learning resource at the Senior High School (SMA) level. The research method used is historical research, there are heuristic, source criticism, interpretation, and historiography. The results show that Vihara Amurva Bhumi Blahbatuh represents the integration of two worship traditions, namely Buddhist and Chinese. The vihara was officially established in 1988, but it has a long historical foundation, dating back to the establishment of a bio in the 1800s. The transformation of this place of worship is closely tied to the religious dynamics of the Chinese community in Blahbatuh Village. Cultural acculturation between Chinese, Buddhist, and Balinese traditions is reflected in the vihara’s architecture, religious ceremonies, worship facilities, and arts. Vihara Amurva Bhumi Blahbatuh holds potential as a historical learning resource. The historical aspects of the vihara are relevant to the curriculum on the history of the New Order government. Additionally, the vihara offers opportunities for character development in alignment with the Pancasila Student Profile. Keywords: acculturation, Chinese, learning resources, monastery